Promotional tool in Guardian SS 15 / Lailatul Noreen Md Noordin - Md Noordin, Lailatul Noreen (Faculty of Business and Management, 2009)
The purpose of study this study is to explain about the application of marketing communication tools that mostly Guardian SS15 Subang Jaya used for January 2009 until October 2009 that generate their income. Conclusion suggest that the company should apply more to personal selling more accurately that will give them benefit to use the method as combine to the 4 element also.